Antioxidant, Antimicrobial and Antiangiogenic Properties of Corylus Avellana Essential Oil Nanoemulsion (CAEO-NE) - Homa Gholami; Masud Homayouni Tabrizi; Touran Ardalan (Fasa University of Medical Sciences, 2021)
Background & Objective: Corylus avellana essential oil (CAEO) due to its individual phytochemicals and phenolic compounds has been recognized as a potent cell-protective compound against oxidative stresses. In the current study, CAEO was encapsulated in the nanoemulsion drug delivery system to improve its bioactivity properties assuming antioxidant, antimicrobial, and anti-angiogenic potentials. Materials & Methods: CAEO nanoemulsions (CAEO-NE) were synthesized applying a high energy ultrasonic method for the emulsification processes and were characterized by DLS, AFM, and SEM analysis. Their antioxidant activity was evaluated by measuring the radical scavenging effect on both DPPH and ABTS free radicals. The CAEO antibacterial and antiangiogenic potentials were studied by measuring the non-growth ring diameter of the staphylococcus aureus culture plate and monitoring the blood vessels of the chick chorioallantoic membrane and its length, respectively. Results: The 45.9-nm CAEO-NE significantly inhibited both DPPH and ABTS free radicals. Meaningful antibacterial and antiangiogenic impacts were detected following increasing CAEO-NE treatment doses (P-value < 0.001). Conclusion: CAEO-NE exhibited three key medicinal activities (antioxidant, antibacterial, and antiangiogenic), which make it a potentially safe antibacterial compound. It is suggested that CAEO-NE has anticancer potential due to its antioxidant and antiangiogenic effects. However, further in vitro and in vivo studies are required to verify its mentioned bioactivities and define details of its mechanism.